DESIGNING GAMES APPLICATIONS FOR EARLY CHILDHOOD UNDERSTANDS THE SELECTION OF COLOURS AND IMAGES IN N INTERACTIVE TEACHING AND LEARNING PROCESS USING TECHNOLOGY - Erza Muhammad Randi; Rima Tamara Aldisa (International Journal of Teaching and Learning, 2024)
Early childhood education is an important stage in the formation of child development. In this context, the use of technology, especially through game applications, offers great potential to increase children's interaction and learning in a fun and interactive way. This training aims to develop game applications specifically designed for early childhood education, with a focus on basic conceptual learning such as numbers, letters, colors, images and shapes. Through collaboration between app developers, educators, and parents, it not only aims to improve children's academic skills, but also promotes positive interactions between children and technology, while ensuring proper supervision and mentoring from adults. It is hoped the development of this application will provide valuable additional knowledge in efforts to improve quality of early childhood education through innovative and fun learning approaches in understanding selection of colors and images.